Does financial literacy, educational level, age, and financial planning affect msmes’ financial behaviour in pontianak? - Fifani Anggraini, Cinthia; Fahruna, Yulyanti; Wendy, Wendy; Mustaruddin, Mustaruddin; Permata Gusti, Girang (SEAN Institute, 2024)
Micro, small and medium-sized enterprises are industries that play a major role in the Indonesian economy, are the largest absorbers of labour and have a significant contribution to the GDP. However, MSME's key role in GDP does not exclude the possibility of bankruptcy. This research analysed four factors influencing financial behaviour: financial literacy, age, educational level, financial planning, and the ability to manage finance as a moderation variable. Financial behaviour is an essential thing that can be done to advance an ongoing business and to organise, process, and plan the finances of an enterprise. This study will examine the impact of financial literacy, educational level, age, and financial planning on MSME's financial behaviour in Indonesia. Using SPSS, the study tested the relationship between independent and dependent variables with moderation variables to support the developed hypothesis. The data collection method uses a questionnaire with a total of 294 respondents. Financial literacy, education, and financial planning had a positive impact, while age had a negative impact.